Electrochromic Os(II)‐Based Metallo‐Supramolecular Polymers. Issue 22 (30th July 2018) - Bera, Manas Kumar; Chakraborty, Chanchal; Rana, Utpal; Higuchi, Masayoshi
Abstract: This work presents the preparation of a series of novel Os(II)‐based metallo‐supramolecular polymers (polyOss: linear polyOsL1100% and hyperbranched polyOsL1x% L2y% ) that show a broad absorption spanning 312 to 677 nm and a low Os(II)/(III) redox potential of 0.94 V. The electrochromic properties of a polyOs film cast on an ITO substrate is investigated. The change in transmittance (Δ T ) of polyOsL1100% is 49.9%, and the switching times for coloration ( t c ) and bleaching ( t b ) are 0.70 and 0.82 s, respectively. The introduction of a 10% branching structure (polyOsL190% L210% ) further enhanced the electrochromic performance with Δ T  = 59.4%, t c  = 0.41 s, and t b  = 0.54 s. The coloration efficiency (η) increased from 396.1 to 467.5 cm 2  C −1 upon branching. A solid‐state electrochromic device with polyOsL1100% is successfully fabricated to use the polymer for potential applications. Abstract : Os(II)‐based metallo‐supramolecular polymers are prepared for the first time to be used in electrochromic applications. The structural features as well as the optical, electrochemical, and electrochromic properties are explored. These polymers show very good electrochromic performance with a large color contrast, short switching time, and high coloration efficiency.